Ruínas e memórias no neoextrativismo mineiro: a construção do desastre da Samarco como trauma cultural - Santos, Natanael de Alencar (Universidade Federal de São Carlos, 2025)
In a global context marked by the devastation of mining, this study investigates how collectives affected by the Samarco dam collapse in Mariana articulate their memories and social suffering to address long-term social damages. The primary objective is to examine the impact of this work of memory on the collective identities of the affected populations and on their relationship with mining enterprises. The research posits that the critical event triggered a situation of sustained social suffering, from which a new structure of feeling emerged among the affected communities. Furthermore, it is argued that the identity-related consequences of the Samarco disaster were of such magnitude that the event can be conceptualized as a cultural trauma. To support these claims, the research draws upon key theoretical frameworks from the fields of Political Ecology, Sociology of Disasters, and Sociology of Culture. The methodology employed is qualitative, centered on documentary and content analysis. Specific materials analyzed include editions of the newspaper Jornal A Sirene, damage matrices produced by organizations dedicated to defending the rights of the affected individuals, and documents from the Campanha Revida Mariana. Additionally, the study incorporates considerations derived from data collected through fieldwork. By examining the memories that emerge from the ruins within mining neoextractivism, the nascent structure of feeling, the future perspectives they engender, and the degree to which the intentions, experiences, and conceptions of the affected subjects are materialized in the disputes over reparation, this research contends that these expedients are crucial for a more precise interpretation of the type, intensity, duration, and forms of damage mitigation resulting from the disaster under consideration.
Ruins and memories in mining neo-extractivism: the construction of the Samarco disaster as cultural trauma
Keywords: Desastre da Samarco; Mariana; Neoextrativismo; Memória coletiva; Trauma cultural; Sofrimento social; CIENCIAS HUMANAS::SOCIOLOGIA; 10. Redução das Desigualdades